2010
DOI: 10.1136/jnnp.2009.204081
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, neuroimaging and neuropathological features of a new chromosome 9p-linked FTD-ALS family

Abstract: Background-Frontotemporal dementia-amyotrophic lateral sclerosis (FTD-ALS) is a heritable form of FTD, but the gene(s) responsible for the majority of autosomal dominant FTD-ALS cases have yet to be found. Previous studies have identified a region on chromosome 9p that is associated with FTD and ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
172
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(197 citation statements)
references
References 28 publications
22
172
3
Order By: Relevance
“…Sections of cerebellar cortex immunostained for DPR with poly‐GA antibody showed small rounded or oat‐shaped NCI within granule cells, though occasionally larger, more rounded and solid NCI (as described in reference [8]) were seen (Figure 1 d ). A few, thin and short neuritic profiles (DN) were seen, and neuronal intranuclear inclusions (NII) were occasionally observed.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Sections of cerebellar cortex immunostained for DPR with poly‐GA antibody showed small rounded or oat‐shaped NCI within granule cells, though occasionally larger, more rounded and solid NCI (as described in reference [8]) were seen (Figure 1 d ). A few, thin and short neuritic profiles (DN) were seen, and neuronal intranuclear inclusions (NII) were occasionally observed.…”
Section: Resultsmentioning
confidence: 74%
“…Positive cases were defined where p62‐positive, TDP‐43‐negative NCI within either the cerebellum (see [8]) or hippocampus (see [7]) could be clearly seen under low power objective (×20) and the majority of high power fields (×40) contained at least two NCI. Either negative cases were completely devoid of p62 immunostaining, or small amounts of apparently extracellular and ‘extraneous’ p62‐positive particulate material was observed in occasional high power fields.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A total of 5 mg of DNA was fragmented with a Bioruptor (Wolf Laboratories Ltd, York, UK) at 30 s on/off bursts for 45 mins to sizes of 200-300 bp. End repair was followed by addition of adenine ends and ligation of adaptors (Illumina, Little Chesterford, Essex, UK) and peak sizes checked using a Bioanlayzer (Agilent Technologies, Wokingham, UK).…”
Section: P212 Locus-capture and Sequencingmentioning
confidence: 99%
“…3,4 Linkage was subsequently confirmed in eight other dominant kindreds defining a minimal overlapping region of B3.6 Mb. 5,6 Genome-wide association studies in sporadic and familial ALS demonstrated highly significant association with single-nucleotide polymorphisms (SNPs) across a 170-Kb region at 9p21.2. [7][8][9][10][11] A massive GGGGCC hexanucleotide repeat expansion mutation (HREM) has recently been identified within intron 1 of C9ORF72 as the pathogenic mutation responsible for familial and sporadic ALS and FTD in these cases.…”
Section: Introductionmentioning
confidence: 99%